Influence Of Culture to Badjao Students’ Attitude Towards Academic Performance - Florinda P. Geyrozaga; Ana Leah Dungog-Cuizon (Zien Journals, 2021)
The increasing rate of dropouts and failures of Badjao students is very alarming. This study described the influence of Culture to Badjao students’ attitude towards academic performance. The researcher wants to see if there are possible ways in which culture is applied in studies and if there are ways to improve their performance in school and avoid sinking performance of grades. This study examines the social exclusion confronting the Badjao people, the sea nomads of the Philippines, through discourse analysis, narrative inquiry, and participant observation. This program was designed to address the prevalent issues of low academic performance of Badjao students due to culture and poverty. The idea was to introduce and reinforce the importance of obtaining an education to have a better future. This uses qualitative kind of research with multiple case method using SWOT Analysis. In regard to the Social Learning Theory by Vygotsky, within the data collected, socializing has been seen as hindrance towards their learning because of certain actions such as bullying towards them. The thesis concludes that social affiliations most particularly in engagement and attendance to events like weddings, interment and thanksgiving influenced SHS Badjao students’ views towards their academic performances. One recommendation for the betterment of the performance of SHS Badjao students is to implement an action plan made by the researcher which specify certain activities at a given period of time.
Keywords: Badjao; Drop- outs; Sea Nomads; Education